PROSPECTS FOR THE INTRODUCTION OF ISLAMIC INSURANCE IN THE REPUBLIC OF UZBEKISTAN - Dildora Muradova; Alisher Eshov (Journals Park Publishing, 2023)
This research paper provides the introduction of Islamic insurance mechanisms in Uzbekistan, as well as new opportunities for the economy and the country.
Keywords: Islamic economics, Islamic model, Islamic insurance, functions of banks, prospects for the introduction.